Case report of Chagas disease reactivation: new diagnosis tool by direct microscopic observation of biopsy specimen and its preservation fluid - Constanza Lopez-Albizu; Martín Pablo Bravo; Marisa Pico; Marisa L. Fernandez (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract Chagas Disease is caused by Trypanosoma cruzi. This infection is endemic in the Americas region. Neurological Chagas reactivation is diagnosed through the visualization of the parasite in the cerebrospinal fluid, blood, or tissue samples. Herein, we report the visualization of trypomastigotes by direct microscopic observation of a brain biopsy specimen and its preservation fluid (PF) in a paitient infected with VIH and T. cruzi. This easy and simple diagnostic method coupled with quantitative polymerase chain reaction can be used in all tissue biopsies and PF of T. cruzi seropositive patients, suspected of Chagas disease reactivation.